Implementation of Project-Based Visual Programming Modules on Problem-Solving Skills Information Technology Education students to Support the SDG’s - Hasanah, Fitria Nur; Wiguna, Akbar; Shofiyah, Noly; Handayani, Nuri Fitri (Universitas Negeri Semarang, 2024)
Students in the Information Technology Education program need to master programming languages as an essential part of their competencies to support educational goals. One of the courses that require programming proficiency is Visual Programming or desktop-based programming. Problem-solving skills are crucial in the development of desktop-based applications. This study aims to analyze the visual programming problem-solving abilities of PTI students in supporting the SDGs through the implementation of the project-based visual programming module. This research employs a quantitative approach with a pre-experimental design of the One-Group Pretest-Posttest type. The sampling technique used is purposive sampling, involving 15 students currently taking the object-oriented programming course. The data used in this study consists of the test results of problem-solving abilities through the final project. Based on the analysis, the project-based visual programming module has been proven effective in improving students' problem-solving skills, as indicated by the paired sample t-test with a significance value of 0.002 < 0.05. In conclusion, there is a significant difference in students' problem-solving abilities before and after using the project-based module. The improvement in students' problem-solving skills through this module is considered high, with an N-Gain score of 0.839.